Effect of Therapeutic Inhibition of TNF on Circulating Endothelial Progenitor Cells in Patients with Rheumatoid Arthritis. (9th October 2013) - Spinelli, F. R.; Metere, A.; Barbati, C.; Pierdominici, M.; Iannuccelli, C.; Lucchino, B.; Ciciarello, F.; Agati, L.; Valesini, G.; Di Franco, M.
Abstract : Endothelial dysfunction has been detected in RA patients and seems to be reversed by control of inflammation. Low circulating endothelial progenitor cells (EPCs) have been described in many conditions associated with increased cardiovascular risk, including RA. The aim of this study was to investigate the effect of inhibition of TNF on EPCs in RA patients. Seventeen patients with moderate-severe RA and 12 sex and age-matched controls were evaluated. Endothelial biomarkers were tested at baseline and after 3 months. EPCs were identified from peripheral blood mononuclear cells by cytofluorimetry using anti-CD34 and anti-vascular endothelial growth factor-receptor 2. Asymmetric dimethylarginine (ADMA) was tested by ELISA and flow-mediated dilatation (FMD) by ultrasonography. Circulating EPCs were significantly lower in RA patients than in controls (P = 0.001 ). After 3 months EPCs increased significantly (P = 0.0006 ) while ADMA levels significantly decreased (P = 0.001 ). An inverse correlation between mean increase in EPCs number and mean decrease of DAS28 after treatment was observed (r = − 0.56, P = 0.04 ). EPCs inversely correlated with ADMA (r = − 0.41, P = 0.022 ). No improvement of FMD was detected. Short-term treatment with anti-TNF was able to increase circulating EPCs concurrently with a proportional decrease of disease activity suggesting that therapeutic intervention aimed at suppressing the inflammatory process might positively affect the endothelial function.